(untitled) (Applied Biological Research, 2014)
An experiment was conducted at SKAUST-K, Wadura (Kashmir) during kharif (summer) 2011 to study the response of French bean (Phaseoulus vulgaris) to various levels of sulphur and boron, applied in the form of gypsum and boric acid, respectively. The treatment combination 45 kg S + 1.0 kg B ha-1gave significantly higher seed and stover yield showing 27.1 and 40.8% increase, respectively, over control. This treatment also gave maximum gross and net returns while treatment combination of 30 kg S and 1.0 kg B ha-1gave maximum returns per rupee. The soil pH was significantly reduced with the application of 45 kg S ha-1, however sulphur and boron had no effect on soil electrical conductivity and organic carbon. Significantly higher total-, organic-, SO4- and adsorbed- sulphur was in soils where S @ 45 kg ha-1 was applied. The non-sulphate S was significantly reduced with increasing S level. Boron had no effect on the forms of S, except SO4-S which showed significant increase with 1.5 kg B. Also, 1.5 kg B had significantly higher total boron content. The treatment combination 45 kg S and 1.5 kg B showed higher available soil nutrients viz., nitrogen, phosphorus, potassium, sulphur and boron.